El nivel de ingreso y su incidencia en el bienestar socio económico en los hogares de la parroquia San Carlos, cantón Quevedo, período 2006-2014 - Arteaga Mayorga, Clara Beatriz (2016)
This research project is based on the analysis of income level and its impact on the socio-economic welfare of households in the parish San Carlos, from the period 2006 to 2014. The results show that the primary and secondary education according to the 2010 census regarding surveys in 2014 has a selective increase. Because they have increased infrastructure conducive to improving the quality of education. The socio-economic situation has also been favorable, in terms of income, housing, social security, education, etc. The current socio-economic situation than that of recent years. Recent research aims to determine the level of socio-economic welfare of the families of the parish San Carlos Quevedo Canton and its relation to the income earned in the period 2006-2014. The specific objectives of this research; Determine the constitution of labor demand, depending on household income of the parish San Carlos, establish the relationship between education level and income of the inhabitants of the parish of San Carlos, analyze the evolution of the socio-economic situation the population of the parish San Carlos, 2006-2014 period. The economic situation in various Latin American countries as Venezuela, Colombia, Peru, and Argentina was also revised etc. In order to obtain more information for this research. Finally it was determined that the homes of San Carlos are dissatisfied with the current situation living in the parish, labor demand is less than the labor supply for this reason many people are unemployed.